2021
DOI: 10.1016/j.bbih.2021.100217
|View full text |Cite
|
Sign up to set email alerts
|

Bell’s Palsy after second dose of Pfizer COVID-19 vaccination in a patient with history of recurrent Bell’s palsy

Abstract: Objective To report a patient with history of recurrent Bell’s Palsy who developed Bell’s Palsy 36 hours after the administration of the second dose of the Pfizer-BioNTech COVID-19 vaccine. Case The patient is a 57-year-old female with past medical history of 3 episodes of Bell’s Palsy. She responded to prednisone treatment and returned to her baseline after each occurrence. Less than 36 hours following the second dose of the vaccine, the patient developed a left Bell’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 4 publications
2
59
0
1
Order By: Relevance
“…4 In a 57yo man with a history of two previous facial palsies, a third Bell's palsy developed 36 h after the second dose of an mRNA-based SARS-CoV-2 vaccine. 5 Facial palsy has been also reported in a study of patients undergoing a SARS-CoV-2 vaccination with mRNA-based vaccines. 6 There is also one report about a deep venous thrombosis (DVT) following the second dose of an mRNA vaccine.…”
mentioning
confidence: 76%
“…4 In a 57yo man with a history of two previous facial palsies, a third Bell's palsy developed 36 h after the second dose of an mRNA-based SARS-CoV-2 vaccine. 5 Facial palsy has been also reported in a study of patients undergoing a SARS-CoV-2 vaccination with mRNA-based vaccines. 6 There is also one report about a deep venous thrombosis (DVT) following the second dose of an mRNA vaccine.…”
mentioning
confidence: 76%
“…Repajic et al reported the first case of Bell's palsy following the 2nd dose of Pfizer-BioNTech COVID-19 vaccination in a 57-year-old Caucasian female. She was treated with prednisone and an antiviral agent, and her symptoms started to improve from the 14 th day [ 17 ]. Their choice of antiviral treatment is not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, considering the biological plausibility, FDA recommends surveillance for cases of Bell's palsy with the deployment of the Moderna COVID-19 Vaccine into larger populations. [6] However, it is imperative that such observations are cautiously widened to include other neurological comorbidities. The temporal relationship of MG exacerbation in our patient strongly suggests that it was related to the mRNA-1273 vaccination.…”
Section: Discussionmentioning
confidence: 99%